2012
DOI: 10.1161/strokeaha.111.635953
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Carotid Plaque Stability Based on the Dynamic Enhancement Pattern in Plaque Components With Multidetector CT Angiography

Abstract: Background and Purpose-Recent studies have investigated plaque morphology to determine patients who are at high risk of carotid atherosclerosis. In this study, we investigated whether a difference in dynamic enhancement pattern in plaque components could be useful to assess plaque stability with multidetector CT angiography. Methods-Fifty-nine lesions with moderate to severe carotid atherosclerosis in 51 patients (33 symptomatic, 18 asymptomatic) were consecutively included. Early-and delayed-phase images were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 32 publications
0
24
1
5
Order By: Relevance
“…Regarding this significant reduction in attenuation going from 66 to 86 keV, we think that the enhancement of the carotid arteries may play a role. 11,12 Some recently published investigations have demonstrated that carotid artery plaques analyzed by CT can show contrast enhancement, 12,13 and Saba et al 13 demonstrated that the degree of intraplaque neovascularization is statistically associated with carotid plaque enhancement. Therefore, it is likely that the molecules of contrast medium get into carotid plaques because they are vascularized.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding this significant reduction in attenuation going from 66 to 86 keV, we think that the enhancement of the carotid arteries may play a role. 11,12 Some recently published investigations have demonstrated that carotid artery plaques analyzed by CT can show contrast enhancement, 12,13 and Saba et al 13 demonstrated that the degree of intraplaque neovascularization is statistically associated with carotid plaque enhancement. Therefore, it is likely that the molecules of contrast medium get into carotid plaques because they are vascularized.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely related to the presence of neovascularization within unstable plaques leading to increase washout of contrast on delayed images. 42 Other MDCTA findings associated with symptomatology include a fissured fibrous cap and LRNC. 88,120 A summary of CT characteristics of stable and vulnerable plaques is provided in Table 2.…”
Section: 121mentioning
confidence: 99%
“…32 Furthermore, many patients with a high degree of stenosis have stable plaques that are thought to be at low risk of rupture. 42 Because of such findings, over the last decade there has been a paradigm shift on the imaging-based risk stratification of carotid disease from static measurements of carotid artery stenosis to characterization of the dynamic biological processes occurring within carotid plaques. It is important for neurosurgeons to be aware of this paradigm shift as it allows for improved risk stratification of patients with both high-and low-degree carotid artery stenosis.…”
mentioning
confidence: 99%
“…However, the reproducibility and utility of this modality for clinical care are not well established [76]. On CT, the identification of plaque neovascularization is based on few studies [77][78][79][80][81] that demonstrated the ability of CT to detect contrast plaque enhancement (CPE) related to the degree of neovascularization (Fig. 7).…”
Section: The Plaque Neovascularizationmentioning
confidence: 99%